Control and Management of Wild Hogs in Florida - William M. Giuliano; George W. Tanner (EDIS)
Florida's wild hogs (Figure 1) are often referred to as feral hogs or swine and are of three general types. These include free-ranging swine that come from domesticated stock, Eurasian wild boar, and hybrids of the two. Although technically, feral refers to free-ranging animals from domesticated stock, all wild hogs are typically referred to as feral in Florida and all are considered the same species, Sus scrofa. Wild hogs are in the family Suidae (true wild pigs), none of which are native to the Americas. This document is WEC 192 and is one of a series of the Department of Wildlife Ecology and Conservation, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences (IFAS), University of Florida. First published: March 2005. Revised: December 2005.